Stakeholder Meeting on Livestock Bill 2024, ILRI, Nairobi, 5 November 2024 - African Group of Negotiators Experts Support; Centre for Minority Rights Development; International Livestock Research Institute (International Livestock Research Institute, 2024)
In Kenya, livestock encompasses cattle, sheep, goats, camels, poultry, and pigs, along with emerging areas like beekeeping and rabbit farming. The sector is a cornerstone of economic growth, food security, and livelihoods, employing nearly half of the agricultural workforce, contributing about 12% to the national Gross Domestic Product (GDP), and accounting for 40% of the agricultural GDP. Recognizing the sector's essential role in Kenya's economy and food security, the government has embedded livestock into key strategic frameworks, including Vision 2030 and the Bottom-Up Economic Transformation Agenda (BETA). Vision 2030 targets increased productivity, value addition, market expansion, and climate resilience, while Bottom-Up Economic Transformation Agenda (BETA) focuses on boosting livestock productivity, empowering small-scale farmers, and enhancing resilience for pastoral communities—all aimed to create jobs, reducing poverty, and strengthening food security across the country. Additionally, the Kenyan Parliament has previously tabled several bills, including the Livestock Bill 2019, aimed at streamlining the livestock sector through structured regulation, enhanced infrastructure, and the establishment of dedicated institutions for training and marketing. Although this Bill had significant potential to reform the sector, it elicited varied responses from stakeholders, which contributed to delays in its enactment. Consequently, these insights and concerns informed the drafting of the subsequent Livestock Bill 2024. The Livestock Bill 2024 aims to advance sector development through the regulation of inputs and products, investment in research and capacity building, and creation of dedicated agencies and training institutions, among other objectives. Positioned as a comprehensive update, the Bill addresses gaps identified in the Livestock Bill 2019, and in line with Kenya's legislative process, stakeholder feedback is essential for refining the Bill’s provisions. Against this backdrop, the International Livestock Research Institute (ILRI) together with African Group of Negotiators Expert Support (AGNES, and Centre for Minority Rights Development (CMRD) convened a meeting to gather and synthesize stakeholder insights on the Livestock Bill 2024, helping shape further discussions and inform key articles in the Bill.